Efficient expression of a novel α-amylase for reduction of tobacco starch and smoke hazard - Han, Zongchen; Hao, Jie; Zou, Dian; Sun, Zhikang; Zhang, Zekun; Niu, Chenqi; Lu, Qi; Huang, Kuo; Ye, Changwen; Wei, Xuetuan (Frontiers in Microbiology, 2025)
The combustion of excessive starch in tobacco leaves leads to more harmful substances, adversely affecting the sensory properties of tobacco and posing significant risks to human health. Therefore, there is an urgent need to develop specific amylases targeting tobacco starch to address these issues. In this study, 5 different α-amylase genes were selected for recombinant expression in Bacillus amyloliquefaciens BAX-5, and the amyA(LC) (derived from Bacillus amyloliquefaciens MK10163) was confirmed to be the optimal gene. Then, the α-amylase activity was further increased by screening host bacteria BAX-5 and signal peptides SP003 (derived from the dacB gene of Bacillus subtilis 168). Subsequently, the α-amylase properties were characterized, such as temperature tolerance, pH tolerance and metal ion. Through replacement of culture medium, the recombinant strain BAX-5/PT-17SP003amyA(LC) produced the maximum α-amylase activity of 904.91 IU/mL, which was about 4 times higher than that of the original culture medium. Finally, the α-amylase Amy (LC) was applied to the enzyme treatment of tobacco leaves, and the evaluation results showed that α-amylase Amy (LC) could play a positive role in reducing damage and enhancing quality of cigarettes. This research provides a novel enzymatic resource for the development of amylases, and it has enormous market potential and application value.